2018
DOI: 10.1080/03630242.2017.1414099
|View full text |Cite
|
Sign up to set email alerts
|

Norms and stigma around unintended pregnancy in Alabama: Associations with recent contraceptive use and dual method use among young women

Abstract: Unintended pregnancy norms and stigma were associated with contraceptive behavior among young women in Alabama. Findings suggest the potential to promote effective contraceptive use in this population by leveraging close relationships and addressing endorsed stigma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…The fear of pregnancy among adolescents in Kisumu is driven primarily by fears that their community will discover their sexual activity. Our findings build upon previous research examining social stigma of adolescent SRH by adding nuance to the intensity of the fear and how it affects behaviors, with sometimes fatal consequences (Moseson et al 2019;Smith et al 2017;Rice et al 2018;Kaljee et al 2007;Akwara and Idele 2020;Hall et al 2018;Levandowski et al 2012). Inclusion of perspectives from boys and the FGD format where social norms were intentionally explored provides new insights on SRH stigma and the focus on abortion and suicide prevalence are novel insights.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The fear of pregnancy among adolescents in Kisumu is driven primarily by fears that their community will discover their sexual activity. Our findings build upon previous research examining social stigma of adolescent SRH by adding nuance to the intensity of the fear and how it affects behaviors, with sometimes fatal consequences (Moseson et al 2019;Smith et al 2017;Rice et al 2018;Kaljee et al 2007;Akwara and Idele 2020;Hall et al 2018;Levandowski et al 2012). Inclusion of perspectives from boys and the FGD format where social norms were intentionally explored provides new insights on SRH stigma and the focus on abortion and suicide prevalence are novel insights.…”
Section: Discussionsupporting
confidence: 60%
“…Social norms are what is considered acceptable behavior within a community, while social stigma is disapproval and retribution when those norms are violated (Bicchieri 2006;Goffman 1959). In general, social stigma does not lead to decreased adolescent sexual activity but rather decreased disclosure of behavior and use of contraceptives, and increased feelings of social isolation (Kinaro et al 2015;Håkansson et al 2020;Rice et al 2018;Kaljee et al 2007). Fearing social stigma, some adolescents conceal their pregnancies, make decisions without social support, seek unsafe abortions, and/or experience suicidal ideation (Smith et al 2017;Crowley, High, and Thomas 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The concentration index analyses of the wealth-related inequality of unintended pregnancy showed that unintended pregnancy is more distributed in poor women (pro-poor distribution). This is supported by studies that show that stigma and socio-economic inequalities are common problems of unintended pregnancies [ 19 , 21 ]. Most unintended pregnancies occurred in the poorest women due to raped or commercial sex workers [ 46 ].…”
Section: Discussionmentioning
confidence: 78%
“…Unintended pregnancies can reduce the rate of maternal [ 13 16 ] and neonatal [ 17 ] health services utilization, and worsen maternal health outcomes [ 10 , 18 20 ]. Even stigma and socio-economic inequalities are common problems of unintended pregnancies [ 19 , 21 ]. Studies reported that unintended pregnancy is associated with pre-eclampsia, obstetrics bleeding and other maternal complications [ 10 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unintended pregnancy is one of the most serious public health problems that impose major health, economic, and psychosocial costs on individuals and communities, as well as significant emotional damage to women, families, and society ( 32 – 34 ). Besides, unintended pregnancy is associated with preeclampsia, obstetric bleeding, stigma, and socioeconomic inequalities ( 2 , 27 , 35 , 36 ).…”
Section: Introductionmentioning
confidence: 99%